KEMATIAN NEONATAL: PERSFEKTIF DEMOGRAFI SOSIAL DAN PENGARUH FAKTOR SOSIAL DALAM ANGKA KEMATIAN BAYI BARU LAHIR - Raisya Anjani Putri Syawalia; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
Neonatal mortality is a serious global health challenge, especially in countries with low levels of development. Neonatal mortality is the death of a baby born within 7 days of birth, also known as early neonatal/early neonatal and the death of a baby born alive more than 7 days to less than 29 days is called late neonatal mortality. In Indonesia itself, neonatal mortality is still a serious problem although there has been a decline in recent years. From a social demographic perspective, neonatal mortality will be related to factors such as maternal age, education level, economic status, and access to health services. An in-depth analysis of the data shows that social disparities such as access to quality prenatal care, medical care during labor, and neonatal care after birth all contribute to the rate of neonatal mortality. Disparities in access to health services and people's level of education may exacerbate the situation, increasing the risk of neonatal mortality among vulnerable groups.